Les formes du journalisme parlementaire au Devoir - Jean Charron; Jocelyn Saint-Pierre (Communication)
This article analyzes a sample of articles written by the parliamentary correspondents of the Montreal newspaper Le Devoir between 1915 and 2006. It shows that members of the Press Gallery no longer seek, as before, to report the affairs of Parliament, but rather to highlight political events that are considered newsworthy.